Improving Vocabulary Mastery by Explicit Instruction for Elementary Students - Harmades, Demisari (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2024)
Vocabulary mastery is a crucial element in language skills that influences literacy comprehension and communication abilities among elementary students. However, vocabulary teaching methods frequently used in schools still tend to rely on conventional approaches, which are less effective in fostering deep understanding and long-term retention. This study aims to evaluate the effectiveness of explicit teaching in enhancing vocabulary mastery among elementary school students. The research employed a quasi-experimental method with a pretest-posttest control group design, involving 60 students divided into an experimental group (explicit teaching) and a control group (conventional teaching). The study's results indicated that the experimental group experienced a significant increase in vocabulary scores following explicit instruction, with an average score difference of 24.4 points compared to the control group, which showed only a 7.1-point improvement. Statistical tests revealed a significant difference between the two groups (p-Value < 0.05), suggesting the effectiveness of explicit teaching in enhancing students' vocabulary acquisition. Additionally, vocabulary retention was higher in the experimental group two weeks after the posttest, indicating that explicit instruction aids in long-term vocabulary retention. Observations during the learning process also showed increased student participation in the experimental group, reflecting a positive impact on student motivation and engagement. Explicit teaching proved effective in improving vocabulary mastery and student engagement in language learning at the elementary level. This study recommends explicit teaching as an effective method that can be broadly implemented within the elementary education curriculum.